Chemical fractionations and mobilization potentials for some trace metals in reef sediments and corals of Qeshm Island, the Persian Gulf - Ghattavi, Saba; Naji, Abolfazl; Yap, Chee Kong (Elsevier B.V., 2023)
The bioavailability of trace metals in coral skeletons and sediment samples from Larak and Qeshm Islands in the Persian Gulf was investigated using the sequential extraction technique (SET), bioaccumulation measurement and risk assessment indices. The fractionation results and risk assessment indices indicated that Pb at the Qeshm Station and Cd and Zn at both Stations could have adverse biological effects due to high bioavailability. The bioaccumulation rate of metals in different reef species and at different Stations was not significant. The studied coral reefs showed a high tendency for Pb adsorption, so they could be an efficient bioindicator of Pb contamination. Statistical analysis showed that Pb and Zn were mainly from anthropogenic contamination sources, while the other metals were primarily of natural origin. The results indicated that further studies are needed to make a realistic assessment of the discharge of trace metals to the Persian Gulf.